2016
DOI: 10.1186/s40810-016-0018-z
|View full text |Cite
|
Sign up to set email alerts
|

The modulating effects of brain stimulation on emotion regulation and decision-making

Abstract: Background: It has been reported that brain stimulation such as repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) can modulate a variety of cognitions and emotions in humans. rTMS and tDCS studies provide strong possibilities of applications in the manipulation of emotion regulation and decision-making in humans. Methods: We searched the literature by using keywords "rTMS," "tDCS," "emotion regulation," and "decision-making" on PubMed (http://www.ncbi.nlm.ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 85 publications
(154 reference statements)
0
11
0
Order By: Relevance
“…Previous brain stimulation research involving transcranial direct current stimulation (tDCS), as well as rTMS protocols, has indicated that transcranial brain stimulation over the DLPFC improves emotion processing in both healthy and patient populations, by inhibiting negative bias and increasing excitability for positive stimuli (Brunoni et al, 2014;Guo et al, 2019;Ironside, O'Shea, Cowen, & Harmer, 2016;Nitsche et al, 2012). Authors argue that stimulation methods such as rTMS, if applied over the left PFC, can modulate affective processing (Choi, Scott, & Lim, 2016;Schutter & van Honk, 2005). For instance, a study performed in a schizophrenic cohort showed that rTMS improved facial affect recognition (Wölwer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous brain stimulation research involving transcranial direct current stimulation (tDCS), as well as rTMS protocols, has indicated that transcranial brain stimulation over the DLPFC improves emotion processing in both healthy and patient populations, by inhibiting negative bias and increasing excitability for positive stimuli (Brunoni et al, 2014;Guo et al, 2019;Ironside, O'Shea, Cowen, & Harmer, 2016;Nitsche et al, 2012). Authors argue that stimulation methods such as rTMS, if applied over the left PFC, can modulate affective processing (Choi, Scott, & Lim, 2016;Schutter & van Honk, 2005). For instance, a study performed in a schizophrenic cohort showed that rTMS improved facial affect recognition (Wölwer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These studies vary in their methodology and reveal contradictory results with high-frequency right dlPFC rTMS being associated with an increase in attentional bias toward negative stimuli (34), whereas high-frequency left dlPFC stimulation decreased the amygdala response to negative stimuli (35). Additionally, a recent review concludes that rTMS influences cognitive control and the attentional and affective aspects of emotion regulation and that rTMS should be investigated for substance use disordered patients (33, 36).…”
Section: Introductionmentioning
confidence: 99%
“…The tDCS, in fact, leads to a reduction in drug craving through inducing changes in dopaminergic neurotransmission in the brain and reducing cortical arousal (10). In addition, tDCS reduces drug craving through influencing the DLPFC area of the prefrontal cortex (11).…”
Section: Introductionmentioning
confidence: 99%
“…Through the anodal stimulation of the right DLPFC (according to the international 10 -20 system of electrode placement) and the cathodal stimulation of the left supraorbital area of the frontal lobe, tDCS reduces the skin conductance response (SCR) and emotional arousal that, in turn, leads to reduced craving (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation